(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
In this work, we report a comparison between the performance of two samples of commercial PIN photodiodes (SFH206K from Osram and S2506-04 from Hamamatsu) mainly addressing the variation of their current sensitivities with accumulated dose ranging from 0-15 kGy. All the results so far obtained have revealed that the radiation induced currents are linearly dependent on dose rates from 3.65 to 55.64 Gy/h. The current sensitivity of both unirradiated diodes (0.178 nA.h/Gy.mm3) slightly decreases with accumulated dose, namely 0.32%/kGy (SFH206K) and 1.4%/kGy (S2506-04). Although the SFH206K device compares favorably with the S2506-04, both diodes can be considered as a low budge alternative, good enough for on-line dosimetry applications in the field of radiation processing.